2009
DOI: 10.1074/jbc.m109.032144
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Mechanism of Respiratory Complex I

Abstract: Complex I plays a central role in cellular energy production, coupling electron transfer between NADH and quinone to proton translocation. The mechanism of this highly efficient enzyme is currently unknown. Mitochondrial complex I is a major source of reactive oxygen species, which may be one of the causes of aging. Dysfunction of complex I is implicated in many human neurodegenerative diseases. We have determined several x-ray structures of the oxidized and reduced hydrophilic domain of complex I from Thermus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
219
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(240 citation statements)
references
References 56 publications
18
219
0
3
Order By: Relevance
“…Asp-139 resides on a four-helix bundle, which is known to be conformationally flexible based on structural and inhibitorbinding studies (12,23). A likely reason for the observed behavior is the abstraction of the proton from the Asp-139/His-38 ion pair that links to the Q reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asp-139 resides on a four-helix bundle, which is known to be conformationally flexible based on structural and inhibitorbinding studies (12,23). A likely reason for the observed behavior is the abstraction of the proton from the Asp-139/His-38 ion pair that links to the Q reduction.…”
Section: Resultsmentioning
confidence: 99%
“…1) (8,11). Biochemical and structural studies suggest that the reduction of Q activates the proton pump via a conformationaldriven coupling mechanism, accompanied by electrostatic gating (2, 6-8, [12][13][14]. A recent study suggested that water-gated transitions and cooperative electrostatic couplings are also of importance in establishing a functional pump (15).…”
mentioning
confidence: 99%
“…We have not identified any bound zinc atoms in the structure of the core hydrophilic subunits of complex I from T. thermophilus (14,16). Several NMR structures of close ␣-proteobacterial homologues of PdNUMM protein were determined by the Northeast Structural Genomics consortium.…”
Section: Discussionmentioning
confidence: 99%
“…This is the NADH-binding site. In the T. thermophilus enzyme the nicotinamide ring of the bound NADH is positioned on top of the isoalloxazine ring of FMN, like in many other pyridinenucleotide-binding flavoenzymes (Berrisford and Sazanov 2009). Also the motif in the 39-kDa subunit is conserved in homologous subunits of the non-mammalian mitochondrial enzymes.…”
Section: Pyridine-nucleotide Binding Sites In Complex Imentioning
confidence: 99%
“…90Å, representing an 'electric wire' through the enzyme, nearly perpendicular to the inner membrane. The structure of the NADH-reduced enzyme nicely showed how NADH binds to FMN in the 51-kDa subunit (Berrisford and Sazanov 2009). Subunits homologous to those in the T. thermophilus enzyme are found in Complex I from many organisms.…”
Section: Introductionmentioning
confidence: 95%